The Influence of Work Motivation and Work Discipline on Employee Performance - Febriyani Putri Antika (Westscience Press, 2023)
This study aims to determine the motivation variables have a significant effect on performance and work discipline has a significant effect on performance. the the sample in this study was 30 respondents and used multiple linear regression analysis with the following regression equation YY = 4.604 + 0.476X1 + 0.336X2 + e. From the regression equation it can be seen that the work motivation variables are stated to have a significant influence on employee performance. It can also be said that more work motivation will affect employee performance. Work discipline variables have an influence on employee’s performance (Y). this means, every time there is an increase in work discipline will improve employee performance.